2018
DOI: 10.1093/annonc/mdy025
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hyperactive ESR1 fusion proteins in endocrine therapy-resistant breast cancer

Abstract: BackgroundEstrogen receptor-positive (ER-positive) metastatic breast cancer is often intractable due to endocrine therapy resistance. Although ESR1 promoter switching events have been associated with endocrine-therapy resistance, recurrent ESR1 fusion proteins have yet to be identified in advanced breast cancer.Patients and methodsTo identify genomic structural rearrangements (REs) including gene fusions in acquired resistance, we undertook a multimodal sequencing effort in three breast cancer patient cohorts:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
102
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 21 publications
1
102
0
1
Order By: Relevance
“…Known mechanisms of resistance to hormone therapies are complex and include epigenetic regulation of ESR1 expression [5,6], ESR1 mutations [712], alternative splicing events [3], ESR1 truncation and fusion events [13], post-translational modifications [14,15], alterations in the hormone binding domain [7,16], alter-native recruitment sites within the genome [17], differential recruitment of coregulators [18], feedback loops by ER target genes on expression/activity of ER [19 ● ], downstream actions of ER target genes on growth factor pathways and other signaling networks [20,21 ●● ], influences of the tumor microenvironment [22], and many others (Figure 1). The details of these mechanisms are beyond the scope of this review but have been thoroughly described by others [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Known mechanisms of resistance to hormone therapies are complex and include epigenetic regulation of ESR1 expression [5,6], ESR1 mutations [712], alternative splicing events [3], ESR1 truncation and fusion events [13], post-translational modifications [14,15], alterations in the hormone binding domain [7,16], alter-native recruitment sites within the genome [17], differential recruitment of coregulators [18], feedback loops by ER target genes on expression/activity of ER [19 ● ], downstream actions of ER target genes on growth factor pathways and other signaling networks [20,21 ●● ], influences of the tumor microenvironment [22], and many others (Figure 1). The details of these mechanisms are beyond the scope of this review but have been thoroughly described by others [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…When introduced into breast cancer cells, ESR1-CCDC170 proteins enhance ligand-independent growth factor signaling, leading to increased cell aggressiveness and tumorigenesis [13]. To date, ESR1-CCDC170 remains the most frequent gene fusion detected in luminal B breast cancer, and its recurrence has been subsequently supported by several recent studies [5,[16][17][18][19]. In addition, this fusion is also detected as a recurrent event in ovarian cancer, and its presence has been associated with exceptional short-term survival [20].…”
mentioning
confidence: 98%
“…About a quarter of the patients with primary tumor and almost all patients with metastases will present with or eventually develop endocrine resistance [3]. Tremendous efforts have been made to study the mechanism of endocrine resistance, and emerging evidence suggests that ESR1 mutations or fusions that mutate or eliminate its ligand binding domain constitute one of the most important driving mechanisms [3][4][5][6].Recurrent gene fusions resulting from chromosome translocations are a critical class of genetic aberrations causing cancer [7], which have fueled modern cancer therapeutics. Recently, several milestone studies have identified recurrent gene fusions in different types of solid tumors with tremendous clinical impact.…”
mentioning
confidence: 99%
“…High-throughput genotyping of solid tumors and continual monitoring of disease burden through sequencing of cfDNA represent potential clinical applications for NGS technologies. It should be noted that targeted DNA sequencing panels such as MammaSeq™ are far less comprehensive than whole exome sequencing and they do not allow for evaluation of structural variants, which can often lead to gene fusions that function as drivers [34]. Nevertheless, as a focused panels represent cost-effective and useful alternatives to whole exome sequencing for targeted mutation detection.…”
Section: Discussionmentioning
confidence: 99%